Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Pada UMKM Kresna Galeri Di Maumere - Avevia, Yuliana; Andreas Rengga; Lewar, Maria Viviana Nurak (Universitas Nusa Nipa Maumere, 2026)
This study aims to determine the effect of product quality and price on purchasing decisions at UMKM Kresna Galeri in Maumere. This research employed a quantitative approach with an associative research design. The population consisted of 4,050 consumers, and a sample of 100 respondents was selected using the Slovin formula. Data were collected through questionnaires, observation, interviews, and documentation. The data were analyzed using multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results indicate that product quality has a positive and significant effect on purchasing decisions. Price also has a positive and significant effect on purchasing decisions. Simultaneously, product quality and price significantly influence purchasing decisions at UMKM Kresna Galeri in Maumere. These findings suggest that improving product quality and implementing appropriate pricing strategies can increase consumer purchasing decisions.